Validity of different kinematical methods for assessing knee angle during cycling - Fonda, B.; Sarabon, N.; Li, F.-X. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
Bike fitting is an important process to adjust the geometry of the bike to the needs of the cyclist. Seat height is usually the first parameter altered in the procedure. The most common bike fitting method to set the seat height is based on the knee angle when the pedal is in its lowest position, i.e. bottom dead centre (BDC). Knee angle between 25 and 35 degrees when pedal is in the BDC has been linked to a reduction of knee injuries. Bike fitting guidelines do not specify what method to measure knee angle should be used.However, there may be large variations between the methods used, e.g. between dynamic or static measurement. Therefore, the aim of this study was to compare three dynamical methods among each other and against static measure. Thirteen trained cyclists performed three 3-minute trials at different seat heights according to knee angle in BDC measuredwith a static goniometer (25°, 30° and 35°). 13 Thirteen infrared cameras (Vicon system, 250 Hz), high-speed camera (300 Hz), and dynamic goniometer (1000Hz) were used to measure the knee angle during pedaling when pedal was in BDC. Statistically significant differences were found among all three dynamical methods. All three methods have also been found to be substantially different compared to the static measure. In conclusion different kinematic methods induce variation inknee angle measurement. Bike fitting experts should take into account the method used when interpreting knee angle as a parameter in seat height adjustment.